2016
DOI: 10.1007/s00132-016-3349-3
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and treatment of nonadjacent cryptococcal infections at the L1 and S1 vertebrae

Abstract: Cryptococcal spine infections are rare infections that are easy to misdiagnose and difficult to cure. Therefore, we report the case of a 25-year-old man who presented with nonspecific spinal lesions at L1 and S1. The patient underwent surgical removal of the lesions, and specimens were submitted for microbial identification, which identified a cryptococcal infection that was susceptible to amphotericin B. The patient exhibited marked improvement after receiving intravenous amphotericin B and remained asymptoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 14 publications
0
4
0
2
Order By: Relevance
“…The serum cryptoccocal antigen (-) Isolated The vertebral abscess was drained and aspirated Fluconazole 12 weeks of oral fluconazole 12 weeks 12 months Full recovery Joo et al[ 2 ] 66/F L2 Rectal cancer with adjuvant chemotherapy Metastatic tumor Postoperative pathologic examination. CSF culture and cryptococcal antigen (-) Isolated Corpectomy of L2 vertebral body Amphotericin B Fluconazole 1 week of intravenous amphotericin B and fluconazole, then, 1 year of oral fluconazole 12 months 12 months Full recovery Lai et al [ 20 ] 25/M L1, S1 No Osteosarcoma Preoperative biopsy revealed an infected lesion, postoperative microbial identification revealed cryptococcal infection Disseminated Lumbosacral debridement Amphotericin B 4 weeks of intravenous amphotericin B and then 8 weeks of oral amphotericin B 12 weeks 9 months Full recovery Li et al [ 17 ] 17/F L1 Immune hemolytic anemia Tuberculosis C. neoformans was isolated in CSF cultures. CSF cryptococcus antigen (+), Preoperative specific stains for C. neoformans (+) Isolated Spinal debridement and fusion Fluconazole 3 months of oral fluconazole Unclear 3 months Full recovery Nankeu et al [ 10 ] ...…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The serum cryptoccocal antigen (-) Isolated The vertebral abscess was drained and aspirated Fluconazole 12 weeks of oral fluconazole 12 weeks 12 months Full recovery Joo et al[ 2 ] 66/F L2 Rectal cancer with adjuvant chemotherapy Metastatic tumor Postoperative pathologic examination. CSF culture and cryptococcal antigen (-) Isolated Corpectomy of L2 vertebral body Amphotericin B Fluconazole 1 week of intravenous amphotericin B and fluconazole, then, 1 year of oral fluconazole 12 months 12 months Full recovery Lai et al [ 20 ] 25/M L1, S1 No Osteosarcoma Preoperative biopsy revealed an infected lesion, postoperative microbial identification revealed cryptococcal infection Disseminated Lumbosacral debridement Amphotericin B 4 weeks of intravenous amphotericin B and then 8 weeks of oral amphotericin B 12 weeks 9 months Full recovery Li et al [ 17 ] 17/F L1 Immune hemolytic anemia Tuberculosis C. neoformans was isolated in CSF cultures. CSF cryptococcus antigen (+), Preoperative specific stains for C. neoformans (+) Isolated Spinal debridement and fusion Fluconazole 3 months of oral fluconazole Unclear 3 months Full recovery Nankeu et al [ 10 ] ...…”
Section: Discussionmentioning
confidence: 99%
“…We found only three published cases of cryptococcal osteomyelitis involving the sacrum [ 10 , 20 , 21 ]. Lai et al [ 20 ] reported a case of nonadjacent cryptococcal infection involving L1 and S1 vertebrae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nosotros exponemos, de estas referencias, solo los casos con compromiso de columna vertebral. Posterior a la publicación de Medaris, encontramos tres casos más de osteomielitis vertebral que sumamos a la serie [5][6][7] .…”
Section: Revisión Bibliográficaunclassified
“…La osteomielitis ocurre en 5-10% de los pacientes con enfermedad criptocóccica diseminada [2][3][4] . Las infecciones criptocóccicas esqueléticas aisladas ocurren con menos frecuencia aun, siendo la afección de la columna vertebral una de las más reportadas 1,2,[5][6][7] .…”
unclassified